The rate of decline in fetal hemoglobin following intrauterine blood transfusion in the management of red cell alloimmunization. (April 2022) - O'Riordan, Sarah L.; Ryan, Gillian A.; Cathcart, Barbara; Hughes, Heather; Higgins, Shane; Fitzgerald, Joan; Corcoran, Siobhan; Walsh, Jennifer; Mahony, Rhona; Carroll, Stephen; McAuliffe, Fionnuala M.; McParland, Peter
Abstract: Objective: Hemolytic disease of the fetus and newborn is characterized by fetal anemia, secondary to maternal alloantibody-mediated fetal erythrocyte destruction. Despite our reliance on intrauterine blood transfusion (IUT) to maintain severely affected pregnancies, it remains difficult to predict the fetal response to an infusion of donor blood. Our objective was to determine the daily rate of decline in fetal hemoglobin following one, two, and three transfusions. We also evaluated the relationship between the fetal hemoglobin level and the corresponding doppler measurement of the fetal middle cerebral artery peak systolic velocity (MCA-PSV). Study Design: A prospective observational study of all singleton pregnancies treated with intrauterine transfusion for fetal anemia secondary to maternal alloimmunization at the National Maternity Hospital, a tertiary referral centre, was conducted over a 10-year period (2011–2020). Demographic and clinical data was obtained from the electronic patient records. Ethical approval was granted by the Ethics and Research Committee of the National Maternity Hospital. Results: A total of 90 intrauterine blood transfusions were performed in 41 fetuses affected by maternal alloimmunization, of which 70% (n = 29), 34% (n = 14) and 15% (n = 6) required a 2nd, 3rd, and 4th transfusion, respectively. The mean rate of decline in fetal hemoglobin following the first transfusion was 0.4 g/dl/day (range, 0.12–0.64 g/dl/day). The mean rate of decline was lower after repeat transfusions at 0.27 g/dl/day (range, 0.16–0.45 g/dl/day). The sensitivity of MCA-PSV threshold of 1.5 Multiples of the Median (MoM) to detect moderate-severe anaemia declined with rank of IUT, from 82% after one previous transfusion, to 75% after two or more previous transfusions. No fetal mortality was seen in our series. Conclusion: Knowledge of the expected rate of decline in fetal hemoglobin following an IUT aids in the determination of appropriate timing of subsequent transfusions in a fetus affected by red cell alloimmunization. We observed a reducing rate of daily decline in hemoglobin in fetuses requiring successive transfusions. Our findings suggest a reduced accuracy of the MCA-PSV threshold of 1.5 MoM in determining the optimal timing of 2nd, 3rd, and 4th transfusions.